Transformasi Pendidikan Digital Etika : Tantangan dan Strategi Menuju SDGs 2030 - Greta Paulina; Sarifatul Maulidiyah; Ichsan Fauzi Rachman (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Building a quality life is one of the main visions of the SDGs, so it is important to educate future generations to be able to utilize digital in accordance with good morals and ethics. The writing in this article uses literature study as a data collection method by using previous research as a foundation to provide a comprehensive analysis. Digital ethics education is a challenge as well as a strategy to deal with the development of today’s world. Through digital ethics education, students can be guided to utilize technology as it should be, and avoid misuse. This article is expected to provide an overview of the influence of digital technology on the success of the 2030 SDGs agenda, and how the transformation of ethical digital education can be a decisive step in the success of the SDGs. Keywords: Digital Ethics, Educational Technology, ICT, SDGs 2030